2018
DOI: 10.30612/agrarian.v11i39.5284
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de plantas de tectona grandis sob restrição hídrica

Abstract: O presente estudo teve como objetivo identificar a(s) estratégia(s) de sobrevivência de plantas de Tectona grandis sob déficit hídrico para fomentar programas de melhoramento genético. O trabalho foi conduzido em casa de vegetação coberta com plástico transparente e laterais fechadas com sombrite 50%. As sementes de Tectona grandis foram semeadas em vasos de 12 litros contendo uma mistura de solo, areia e esterco na proporção de 3:1:0,5 respectivamente. Utilizou-se o delineamento experimental inteiramente casu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The plant height, stem diameter, number of leaves, transpiration rate, and total plant weight of plants irrigated with 100% of the retention capacity of the substrate were higher than those of plants under water deficit 13%, 9%, 50%, 50%, and 32%, respectively. The water deficit resulted in lower availability of water for cell expansion and significant restriction to vegetative growth and corroborate those found by Matos, Freitas, Souza and Lopes, (2018) who identified that the initiation and development of the leaf primordium are dependent on the water status of the plant. The emergence and development of leaf primordia are dependent on the plant's water status.…”
Section: Resultssupporting
confidence: 87%
“…The plant height, stem diameter, number of leaves, transpiration rate, and total plant weight of plants irrigated with 100% of the retention capacity of the substrate were higher than those of plants under water deficit 13%, 9%, 50%, 50%, and 32%, respectively. The water deficit resulted in lower availability of water for cell expansion and significant restriction to vegetative growth and corroborate those found by Matos, Freitas, Souza and Lopes, (2018) who identified that the initiation and development of the leaf primordium are dependent on the water status of the plant. The emergence and development of leaf primordia are dependent on the plant's water status.…”
Section: Resultssupporting
confidence: 87%
“…The reduction in number of leaves and growth under water deficit are adjustment strategies to tolerate low water availability, because drought promotes morphophysiological changes with intent to stimulate acclimation and tolerance to the new conditions (Matos, Freitas, Souza, Araújo, & Rosa, 2018) The consonance between biomass and transpiration reflects the variation in water availability in the stomatal conductance and CO 2 diffusion for photosynthesis, because as the water volume provided was increased, the stomata opened, resulting in higher CO 2 influx and water efflux with consequent increase in photosynthesis, and increases in the biomass and transpiration with maximum point at 111% and 118% water regimes, respectively. According to Souza et al (2015), transpiration decreases under low water viability indicating tolerance to water deficit; but other mechanisms are needed to ratify tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The water restriction does not cause significant losses in the survival of seedlings in T. grandis, because it presents a stomata high sensitivity, closing them and thus reducing its leaf area (MATOS et al, 2018). However, in this study there is a decrease in survival values in GH, SH and FS (Table 1), a fact also observed by Badilla et al (2016) for T. grandis in the passage of GH and SH seedlings, 95.37% and 89.93% respectively, and Meza et al (2015) 87.5% in GH and 69.39% in SH.…”
Section: Discussionmentioning
confidence: 99%